1999
DOI: 10.1029/1999gl008341
|View full text |Cite
|
Sign up to set email alerts
|

Dust devil vortices seen by the Mars Pathfinder Camera

Abstract: Abstract. Discovery of dust devil vortices in Mars

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
138
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(156 citation statements)
references
References 16 publications
(8 reference statements)
16
138
0
1
Order By: Relevance
“…Results in Table 4 images [Metzger et al, 1999], and these vortices probably also were associated with rapid, localized changes in wind direction. For these reasons we postpone averaging until later in the data reduction process and report 0 in Table 4 without the effect of aligning deflections along averaged (b, in case some variations of qb within individual S0173 activations are significant.…”
Section: Conversion Of Raw Image Measurements Inmentioning
confidence: 99%
“…Results in Table 4 images [Metzger et al, 1999], and these vortices probably also were associated with rapid, localized changes in wind direction. For these reasons we postpone averaging until later in the data reduction process and report 0 in Table 4 without the effect of aligning deflections along averaged (b, in case some variations of qb within individual S0173 activations are significant.…”
Section: Conversion Of Raw Image Measurements Inmentioning
confidence: 99%
“…For Mars, Metzger et al (1999) used column opacity to estimate the particle loading for a dust devil observed by the Imager for Mars Pathfinder camera. They Renno et al, 1998 andRenno et al, 2000) and the dust load estimate of Metzger et al, (1999) to estimate a flux of 70 mg m -2 s -1 .…”
Section: Comparisonmentioning
confidence: 99%
“…More attempts have been made to estimate dust load for martian dust devils using estimates of optical depth from orbit (Thomas and Gierasch, 1985) and the surface Greeley et al, 2006;Greeley et al, 2010). Thomas and Gierasch (1985) measured a dust load of ~ 30 mg m -3 ; Metzger et al (1999) found a range from 10 to 100 g m -3 . Greeley et al (2006) published data only for estimated flux and again particle loads cannot be estimated from their data without attempting to back-calculate particle loads based on cited average vertical wind speeds and flux data.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Tracks left by the passage of dust devils are found on nearly every region across the Martian surface [Cantor and Edgett, 2002], and nearly every orbiter and lander sent from Earth has directly observed active plumes, including: Viking Landers 1 & 2 (passage of vortex cores inferred by meteorological data) [Ringrose et al, 2003], Viking Orbiters 1 & 2 [Thomas and Gierasch, 1985], Mars Pathfinder Lander [Schofield et al, 1997;Metzger et al, 1999] and Mars Global Surveyor (MGS) [Edgett and Malin, 2000]. Measured diameters were between 28-509 m, with heights of 170 -8500 m. An extensive survey using 2 p.m. Mars Orbiter Camera (MOC) wide and narrow-angle images was conducted by Fisher et al [2005], who determined that Martian dust devils exhibit some regional and seasonal dependence with a bias toward northern latitudes during the warmest seasons.…”
Section: Introductionmentioning
confidence: 99%